Pengaruh Media Sosial Terhadap Penggunaan Bahasa - Nur Aini Fatjeriyah; Faiza Irisaliya Andini; Febrialta Dinda Safira; Moniqe Kurnia Zulkarnain Zulkarnain; Venus Soraya Rizky Ratu Nabilla; Eni Nur Hayati (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The influence of social media has a considerable impact on people's lives. There are lots of new languages created by young people in social media. Considering that social media users have a very high number, there are lots of language changes. The purpose of writing this research is to provide readers with a more in-depth knowledge of the influence of social media in the use of Indonesian in the life of the nation and state. This is proof that there has been a change in Indonesian due to social media. Various new languages have emerged and have contaminated the standard Indonesian language which should be upheld.